In-Company Adaptation of Employees and Employers to Each Other - V. V. Mortikov (Вестник Российского экономического университета имени Г. В. Плеханова, 2022)
Adaptation of employees and employers to each other is very important for resolving many problems of labour economics and HR management. There are four types of response to discrepancy between opportunities and needs of labour relation entities: adjustment of workers to work-place requirements; changes in work-places on the part of employees; changes in work-places by employers necessary to comply with needs and qualification of workers; adaptation of employers to needs and qualities of workers. Adaptation of employers and employees to each other and changing work-places by them act, to a certain extent, as substitutes, which allow labour relation participants to interact effectively. Having faced restrictions by one of the four mentioned response to discrepancy between workers’ characteristics and work-places, the given participants turn to another response. The author using the experience of a university lecturer researches changes in work-place on the part of employees in the system of higher education. To analyze the potential of changing work-place characteristics the data of Risstat selective study was used. Factors showing specific features of adaptation of employees and employers to each other were identified and analyzed. Among them the author mentioned the situation on markets of finished products and labour, where the organization (employer) is involved, professional and personal qualities of worker, budget restrictions of labour relation entities, specific features of labour contracts and legislation.